Development of phycology in Malaysia - Phang, Siew Moi (Springer Verlag, 2018)
Phycological research in Malaysia started in the 1900s with the documentation of both freshwater and marine microalgae and seaweeds, especially those with economic importance. Phycological research has grown and matured from initial diversity and ecological studies to DNA-based research which allowed us to venture into the world of algal biotechnology with focus on phylogenetics, genomics and strain improvement. Our research has expanded towards finding solutions to the declining food and fuel resources to be relevant in today’s world of energy and food crises amidst a changing climate. Sustainability solutions are especially relevant and will continue to drive the development of our seaweed industry and the opportunities for establishment of an algal industry in Malaysia. Algal farming offers many opportunities for research and development activities, and great potential, especially due to the abundant tropical sunshine, long coastline, good infrastructure and global connectivities. This paper is a brief account of the development of phycology in Malaysia, followed by some thoughts on future directions. Our research is supported by two very important collections: (i) the University of Malaya Algae Culture Collection (UMMAC) and (ii) the University of Malaya Seaweeds and Seagrasses Herbarium.